2011
DOI: 10.1109/twc.2011.030311.100402
|View full text |Cite
|
Sign up to set email alerts
|

The 802.11g 11 Mb/s Rate is More Robust than 6 Mb/s

Abstract: Abstract-The robustness to noise of the 802.11b/g 5.5 Mb/s and 11 Mb/s rates must be investigated experimentally as they cannot be predicted theoretically. In this paper we report on detailed outdoor and indoor measurements that lead us to the surprising conclusion that the 11 Mb/s 802.11g rate experiences fewer packet losses than the 6 Mb/s 802.11g rate at any given (symbol) SNR. This occurs due to the combination of modulation and physical layer coding schemes used by these rates and has serious implications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…For the Rician channel, only the 9 Mb/s rate appears redundant. Plots for the AWGN channel can be found elsewhere [8][9] [24] and mimic those shown here for Rician fading. Consequently, all of these channel models suggest redundancy of the 9 Mb/s rate.…”
Section: A Rate-set Characteristicsmentioning
confidence: 83%
See 2 more Smart Citations
“…For the Rician channel, only the 9 Mb/s rate appears redundant. Plots for the AWGN channel can be found elsewhere [8][9] [24] and mimic those shown here for Rician fading. Consequently, all of these channel models suggest redundancy of the 9 Mb/s rate.…”
Section: A Rate-set Characteristicsmentioning
confidence: 83%
“…This scheme has proven resistent to analytic study so that no theoretical framework for their performance analysis currently exists. Using pseudotheory with manufacturer-fit curves and detailed experiments, elsewhere we have shown that the 11 Mb/s rate in 802.11g is more robust that the 6 Mb/s rate [24].…”
Section: A Rate-set Characteristicsmentioning
confidence: 96%
See 1 more Smart Citation
“…7(a)). We suspect it is because 802.11n is more vulnerable to interference than 802.11a, just like how 802.11g could be less robust against interference than 802.11b [9]. When C 1 's ACK power was reduced, C 2 's throughput greatly improved regardless of C 2 's ACK power level.…”
Section: Impact Of Mac Ack Interferencementioning
confidence: 99%
“…Some of these results have been published in [67]. Section 5.2 describes the theoretical analysis of IEEE 802.11a/g rates.…”
Section: Introductionmentioning
confidence: 99%